2018
DOI: 10.1007/s40520-018-0990-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 3 months of detraining on functional fitness and quality of life in older adults who regularly exercise

Abstract: Three months of a detraining period in older people who habitually undertake supervised activities is enough to produce a decline in dynamic balance and also quality of life. To avoid the deleterious effect of periods of cessation of supervised exercise, as a suggestion, specifically designed exercises could be prescribed for an older population, with emphasis on balance exercises.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
37
2
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 36 publications
7
37
2
1
Order By: Relevance
“…Exercise did not provide a protective effect against gait speed losses when exercise was withdrawn, as indicated by a decline in gait speed after detraining (at follow-up), although it should be noted that the overall decline in gait speed from baseline to follow-up was smaller in the exercise group (~0.04 m/s) as compared to the control group (~0.12 m/s). The detrimental effects of detraining on physical function are well known in older persons with and without dementia [11,[68][69][70]. Thus, our results support the recommendation of continuous physical exercise for PwD.…”
Section: Effects Of Exercise On Physical Functionsupporting
confidence: 85%
“…Exercise did not provide a protective effect against gait speed losses when exercise was withdrawn, as indicated by a decline in gait speed after detraining (at follow-up), although it should be noted that the overall decline in gait speed from baseline to follow-up was smaller in the exercise group (~0.04 m/s) as compared to the control group (~0.12 m/s). The detrimental effects of detraining on physical function are well known in older persons with and without dementia [11,[68][69][70]. Thus, our results support the recommendation of continuous physical exercise for PwD.…”
Section: Effects Of Exercise On Physical Functionsupporting
confidence: 85%
“…It should be noted that prepandemic frequent exercisers (e.g., frequency of four days or more) experienced worse mood states if they decreased their exercise frequency during the pandemic. Decrease in exercise levels, known as detraining [ 68 ], can have adverse effects both on exercise-induced physiological adaptation [ 69 , 70 ], as well as psychological adaptations [ 71 ]. Other studies have shown that the cessation of regular exercise is linked to negative mood states [ 72 , 73 ], as well as increases in somatic depressive symptoms (e.g., fatigue, Berlin, Kop, and Deuster [ 72 ]).…”
Section: Discussionmentioning
confidence: 99%
“…The partial or total interruption to habitual PA can lead to deterioration in several metabolic and functional outcomes in older adults. For example, 3 months of detraining has been shown to produce a decline in functional fitness, mental health, quality of life, cardiorespiratory fitness, and lipid, glycemic and haemodynamic profiles in physically active older adults [ 13 , 14 ]. Therefore, older adults who were regularly active before the pandemic should aim to maintain or increase their levels of PA to achieve recommended levels where possible, while complying with local and national regulations.…”
Section: Contextmentioning
confidence: 99%